Winners and losers of early elections: On the welfare implications of political blockades and early elections - Felix Bierbrauer; Lydia Mechtenberg (Max Planck Institute for Research on Collective Goods, 2008)
We develop a dynamic model of political competition. Each party has a policymotivated ideological wing and an office-motivated opportunistic wing. A blockade arises if inner-party conflict stops policy implementation. We use this model to study whether early elections should be used to overcome a blockade. They have the advantage that urgent decisions are no longer delayed, and the disadvantage that unsuccessful governments gain additional time in office. This may give rise to a time inconsistency. Voters are in favour of a constitution without early elections. However, in the middle of a political crisis, they are willing to abandon it.
Keywords: D82; D72; D61; 330; early elections; political blockades; Wahl; Ideologie; Politische Partei; Wettbewerb; Public Choice; Wohlfahrtseffekt; Theorie